Different infusion durations for preventing platinum‐induced hearing loss in children with cancer - van As, Jorrit W (Cochrane Database Syst Rev, 2020)
BACKGROUND: Platinum‐based therapy, including cisplatin, carboplatin or oxaliplatin, or a combination of these, is used to treat a variety of paediatric malignancies. Unfortunately, one of the most important adverse effects is the occurrence of hearing loss or ototoxicity. In an effort to prevent this ototoxicity, different platinum infusion durations have been studied. This review is the third update of a previously published Cochrane Review. OBJECTIVES: To assess the effects of different durations of platinum infusion to prevent hearing loss or tinnitus, or both, in children with cancer. Secondary objectives were to assess possible effects of these infusion durations on: a) anti‐tumour efficacy of platinum‐based therapy, b) adverse effects other than hearing loss or tinnitus, and c) quality of life. SEARCH METHODS: We searched the electronic databases Cochrane Central Register of Controlled Trials (CENTRAL; the Cochrane Library 14 November 2019), MEDLINE (PubMed) (1945 to 14 November 2019) and Embase (Ovid) (1980 to 14 November 2019). In addition, we handsearched reference lists of relevant articles and we assessed the conference proceedings of the International Society for Paediatric Oncology (2009 up to and including 2019) and the American Society of Pediatric Hematology/Oncology (2014 up to and including 2019). We scanned ClinicalTrials.gov and the World Health Organization International Clinical Trials Registry Platform (WHO ICTRP; apps.who.int/trialsearch) for ongoing trials (both searched on 4 November 2019). SELECTION CRITERIA: Randomised controlled trials (RCTs) or controlled clinical trials (CCTs) comparing different platinum infusion durations in children with cancer. Only the platinum infusion duration could differ between the treatment groups. DATA COLLECTION AND ANALYSIS: Two review authors independently performed the study selection, 'Risk of bias' assessment and GRADE assessment of included studies, and data extraction including adverse effects. Analyses were performed according to the guidelines of the Cochrane Handbook for Systematic Reviews of Interventions. MAIN RESULTS: We identified one RCT and no CCTs; in this update no additional eligible studies were identified. The RCT (total number of children = 91) evaluated the use of a continuous cisplatin infusion (N = 43) versus a one‐hour bolus cisplatin infusion (N = 48) in children with neuroblastoma. For the continuous infusion, cisplatin was administered on days one to five of the cycle, but it is unclear if the infusion duration was a total of five days. Risk of bias was present. Only results from shortly after induction therapy were provided. No clear evidence of a difference in hearing loss (defined as asymptomatic and symptomatic disease combined) between the different infusion durations was identified as results were imprecise (risk ratio (RR) 1.39, 95% confidence interval (CI) 0.47 to 4.13, low‐quality evidence). Although the numbers of children were not provided, it was stated that tumour response was equivalent in both treatment arms. With regard to adverse effects other than ototoxicity, we were only able to assess toxic deaths. Again, the confidence interval of the estimated effect was too wide to exclude differences between the treatment groups (RR 1.12, 95% CI 0.07 to 17.31, low‐quality evidence). No data were available for the other outcomes of interest (i.e. tinnitus, overall survival, event‐free survival and quality of life) or for other (combinations of) infusion durations or other platinum analogues. AUTHORS' CONCLUSIONS: Since only one eligible RCT evaluating the use of a continuous cisplatin infusion versus a one‐hour bolus cisplatin infusion was found, and that had methodological limitations, no definitive conclusions can be made. It should be noted that 'no evidence of effect', as identified in this review, is not the same as 'evidence of no effect'. For other (combinations of) infusion durations and other platinum analogues no eligible studies were identified. More high‐quality research is needed.